Early life climate and adulthood mental health: how birth seasonality influences depressive symptoms in adults - Hao Zhou; Danni Peng-Li; Juan Chen; Dong Sun; Bin Wan (BMC, 2023)
Abstract Background Early life in-utero can have long-term influence on the mental health status of individuals in adulthood, such as depression. Age, gender, socio-economic status, education, and geography are demographic factors shown to be particularly vulnerable towards the development of depressive symptoms. In addition, climate risks on depression include sunlight, rain, and temperature. However, whether climate factors in early life have a long-term influence on depression related to demographic vulnerability remains unknown. Here, the present study explored the association between birth seasonality and adulthood depressive symptoms. Methods We employed data from the project of Chinese Labour-forces Dynamic Survey (CLDS) 2016, containing the epidemiological data of depressive symptoms with a probability proportional to size cluster and random cluster sampling method in 29 provinces of China. A final sample size of 16,185 participants was included. Birth seasonality included spring (March, April, and May), summer (June, July, and August), autumn (September, October, and November), and winter (December, January, and February). Results We found that born in Autumn peaked lowest rate of having depressive symptoms (16.8%) and born in Summer (vs. Autumn) had a significant higher ratio (OR = 1.14, 95%CI = 1.02, 1.29) when controlling for demographic variables. In addition, demographic odds ratio of having depressive symptoms differed between people born in different seasons, particular for age and geography. Conclusion Our findings suggest that birth seasonality influences the sensitive link of depressive symptoms with age and geography. It implicates early life climate environment may play a role in the development of adulthood depressive symptoms.